Chemiluminescent Probe for the In Vitro and In Vivo Imaging of Cancers Over‐Expressing NQO1. (9th January 2019) - Son, Subin; Won, Miae; Green, Ori; Hananya, Nir; Sharma, Amit; Jeon, Yukyoung; Kwak, Jong Hwan; Sessler, Jonathan L.; Shabat, Doron; Kim, Jong Seung
Abstract: Activatable (turn‐on) probes that permit the rapid, sensitive, selective, and accurate identification of cancer‐associated biomarkers can help drive advances in cancer research. Herein, a NAD(P)H:quinone oxidoreductase‐1 (NQO1)‐specific chemiluminescent probe 1 is reported that allows the differentiation between cancer subtypes. Probe 1 incorporates an NQO1‐specific trimethyl‐locked quinone trigger moiety covalently tethered to a phenoxy‐dioxetane moiety through a para ‐aminobenzyl alcohol linker. Bio‐reduction of the quinone to the corresponding hydroquinone results in a chemiluminescent signal. As inferred from a combination of in vitro cell culture analyses and in vivo mice studies, the probe is safe, cell permeable, and capable of producing a "turn‐on" luminescence response in an NQO1‐positive A549 lung cancer model. On this basis, probe 1 can be used to identify cancerous cells and tissues characterized by elevated NQO1 levels. Abstract : Eine aktivierbare Chemilumineszenzsonde wurde entwickelt, um endogenes NOQ1 in Zellen und Mäusen ohne die Notwendigkeit zusätzlicher Komponenten abzubilden. Die Vorteile dieser Sonde sind schnelles Ansprechverhalten, gute Selektivität und ein hohes Signal‐Rausch‐Verhältnis.